Kedudukan dan Daya Mengikat Konvensi Denhaag 1954 Tentang Perlindungan Obyek Budaya Dalam Sengketa Bersenjata Terhadap Pihak-Pihak Yang Bersengketa (Amerika Serikat-Irak) Menurut Konvensi Wina 1969 Tentang Perjanjian Internasional - Hilda Hilda (Jurnal Cita Hukum, 2013)
Status and Binding Power of the Denhaag Convention 1954. Armed conflict between the United States and Iraq indicates that the two parties neglect cultural objects. The disobedient towards the provisions of international law, particularly the 1954 Hague Convention and its additional protocols, regarded as one of the conspicuous reasons for the fatal damage of cultural objects. The only justification to avoid from the obligation od protecting cultural objects is that one of the party does not bind to the instrument of international law. This has made the position and power of the Hague Convention 1954 becomes a crucial issue to the extent of its effectiveness. DOI: 10.15408/jch.v1i1.2984